The history of the Jacob Cycle (Genesis 25-35): recent research on the compilation, the redaction, and the reception of the biblical narrative and its historical and cultural contexts - Hensel, Benedikt (Archaeology and bible, 2021)
Das literaturhistorische Wachstum des Jakob-Zyklus wie auch seine historischen Hintergründe sind denkbar komplex und viele Selbstverständlichkeiten der Forschung sind in den vergangenen Jahren in Frage gestellt worden. Der vorliegende Band vereint die neueste Forschung auf diesem Gebiet und schließt insbesondere eine Kombination aus literaturhistorischen, archäologischen und historischen Fragestellungen ein, die der Komplexität der Jakoberzählung gerecht werden.InhaltsübersichtBenedikt Hensel: The History of the Jacob Cycle in Recent Research: An Introduction to the Volume – Konrad Schmid: Shifting Political Theologies in the Literary Development of the Jacob Cycle – Friederike Neumann: Jacob, Laban, and the Two Daughters: Insights into the Formation of the Jacob-Laban-Story (Genesis 29–31) – Benedikt Hensel: Edom in the Jacob Cycle (Gen *25–35): New Insights on Its Positive Relations with Israel, the Literary-Historical Development of Its Role, and Its Historical Background(s) – Jakob Wöhrle: Jacob from Israel and Jacob from Judah: Reflections upon the Formation and the Historical Backgrounds of the Jacob Story – Christian Frevel: Jacob as Father of the Twelve Tribes: Literary and Historical Considerations – Guy Darshan: The Priestly Account of the End of Jacob’s Life: The Significance of Text-Critical Evidence – Aharon Tavger: “And He Called the Name of that Place Bethel” (Gen 28:19): Historical-Geography and Archaeology of the Sanctuary of Bethel